Early Chinese Periodicals Online (ECPO) [metadata] - Arnold, Matthias (Universität, 2022)
ECPO joins several important digital collections of the early Chinese press and puts them into a single overarching framework. In the first phase, ...
Gesehen am 08.12.2022
Keywords: Forschungsdaten; Datenbank